SUN-281 Pituitary Hyperplasia Secondary to Uncontrolled Primary Hypothyroidism - Betancourt, Jessica Lee (J Endocr Soc, 2020)
Background: There are several recognized causes of hyperplasia of the pituitary gland. These may present as sellar masses and be misdiagnosed as pituitary adenomas. Pituitary hyperplasia can occur in the presence of long standing primary hypothyroidism due to the loss of negative feedback caused by decreased secretion of thyroxine (T4) and triiodothyronine (T3) by the thyroid gland, leading to excessive thyrotropin releasing hormone (TRH) production by the hypothalamus causing Thyrotroph pituitary hyperplasia Clinical case: 51 y/o female with a past medical history that includes anxiety & depression, obesity, pre-diabetes and uncontrolled hypothyroidism due to Hashimoto’s, presented to the Endocrinology clinic for recent diagnosis of pituitary macroadenoma. Patient reported tiredness, decrease energy, myalgias, weight gain, abnormal menstrual periods and frontal headaches. On physical exam, she had a body mass index of 37.39kg/m2, blood pressure of 130/85mmHg, heart rate of 91 bpm. There was no thyromegaly noted on exam. No abdominal striae was noted. Overall, exam was unremarkable. Her neurological exam was normal and there were no obvious visual field deficits. Initial laboratory tests revealed a thyroid stimulating hormone (TSH) >150 uIU/mL (0.46–4.7 uIU/mL), free T4 0.3 ng/dL (0.7–1.3 ng/dL) and positive TPO antibodies. Other endocrine work up including ACTH, cortisol, prolactin, FSH, LH and IGF-1, were normal. An MRI of the pituitary revealed a heterogeneous enhancing mass replacing the pituitary gland in the sella that measured 16 x 17 x 11 mm. She was evaluated by Neurosurgery, for presumed diagnosis of pituitary macroadenoma. However, prompt recognition of uncontrolled primary hypothyroidism causing pituitary hyperplasia lead to medical management, first. She was started on weight based (1.6mcg/kg/day) levothyroxine at 175 mcg per day. Six weeks after thyroid replacement therapy laboratory evaluation showed improvement in thyroid function test with a TSH of 0.8mIU/mL, free T4 2.8ng/dL and total T3 307ng/dL. A repeat MRI of the pituitary showed decrease in size of the pituitary gland measuring 15 x 4 x 10 mm. Conclusion: This case illustrates the importance of early recognition of uncontrolled primary hypothyroidism during the evaluation of a pituitary mass. Complete regression of this pituitary gland abnormality can be achieved with thyroid hormone replacement avoiding the irreversible consequences of inappropriate pituitary surgery.